Superior Mesenteric Vein Thrombosis Secondary to Oral Contraceptive Use - Heather Stewart; Michael T. Flannery; Deborah A. Humphrey (Case Reports in Vascular Medicine)
Superior mesenteric vein thrombosis (SMVT) is a rare yet frequently fatal cause of intestinal ischemia. Despite its severe consequences, SMVT often presents with nonspecific symptoms such as nausea, vomiting, and abdominal pain. It can occur with or without gastrointestinal bleeding, and symptoms may be present for hours to weeks. Physical exam can vary from a benign to an acute abdomen. The are no specific diagnostic laboratory studies for the presence of MVT, and it can be an incidental finding of computed tomography or ultrasound. Patients at risk for MVT include those with a history of a hypercoagulable state or secondary cases such as sepsis, gastrointestinal malignancy, liver disease, pancreatic pathology, abdominal surgery and medications. The authors present a case of a patient presenting with acute abdominal pain and ultimately a SMVT secondary to oral contraceptives by exclusion.